Novel design of a smart and harmonized flexible printed coil sensor to enhance the ability to detect defects in pipes. (April 2019) - Tse, P.; Fang, Z.; Ng, K.
Abstract: The interaction between the static and dynamic magnetic fields generated from a conventional magnetostrictive sensor (MsS) is an important factor in the sensitivity of defect detection. Normally, the dynamic magnetic field of an MsS is generated by its electric coils, whereas the static magnetic field is generated by permanent magnets. The magnitude of the generated fields and their interactions significantly affect the amplitude of the induced guided-wave signals. The conventional hard coil-based MsS is usually bulky and is not sufficiently flexible to fit pipes of various sizes. Such inflexibility limits the use of conventional MsS in practical situations. To overcome these limitations, the authors designed an innovative type of coil, called the flexible printed coil (FPC), to replace the inflexible hard coil. Because the FPC is a thin film, it can be easily wrapped around any size pipe, whereas the conventional hard coil–based MsS requires modification with changes in the size of pipes. Although the smart FPC-MsS can work as expected, due to the design of the flexible coils, the interference caused by the coils exerted an uneven magnetostrictive force on the tested pipe. This increases the sensitivity required to detect defects, which differ at each circumferential location of the inspected pipe. Hence, the smart FPC-MsS generates different results at different circumferential locations even though the sizes of the cracks are the same at each circumferential location. To address this deficiency, we designed a smart and harmonized FPC-MsS, called smart HFPC-MsS, which can generate an even magnetostrictive force regardless of the circumferential location of the crack. Ultimately, an evenly distributed amplitude of guided waves can be emitted into the entire pipe, which improves the accuracy of crack detection. In this paper, the theoretical foundation of designing the smart HFPC-MsS is explained, and its working principles are introduced. Both the simulated and experimental results prove the effectiveness of such a novel HFPC-MsS, and the results show that it can generate even amplitude of the guided waves to the pipe regardless of the circumferential location of the crack, resulting in more accurate crack detection than that provided by the author's previously designed smart FPC-MsS.